2015
DOI: 10.3390/ijerph120403453
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Community Readiness Tool Applications: Implications for Reporting

Abstract: Background: A systematic review characterised and synthesised applications of the Community Readiness Tool (CRT) and synthesised quantitative results for readiness applications at multiple time points. Methods: Eleven databases in OvidSP and EBSCHOhost were searched to retrieve CRT applications. Information from primary studies was extracted independently by two researchers. Results: Forty applications of the CRT met inclusion criteria focussing on 14 different health and social issues. The community of intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 30 publications
5
48
0
4
Order By: Relevance
“…The PCLR online tool is responsive to time and resource constraints associated with conventional over-the-phone applications of the CRT. 19 This study unmasks suburb-level heterogeneity in PCLR that exists within communities. Although some communities had homogeneous profiles, suburb-level variation in PCLR scores was observed for most.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCLR online tool is responsive to time and resource constraints associated with conventional over-the-phone applications of the CRT. 19 This study unmasks suburb-level heterogeneity in PCLR that exists within communities. Although some communities had homogeneous profiles, suburb-level variation in PCLR scores was observed for most.…”
Section: Discussionmentioning
confidence: 99%
“…18,[23][24][25][26] Community readiness, and in particular PCLR, can change in 2-3 intervention years particularly when interventions, like OPAL, explicitly target community leaders. Previous research has reported on the full CRT assessment, 19 and although the present study presents data only on the leadership dimension of the CRT, it assesses leadership readiness on a much larger scale than has been previously attempted. In a recent systematic review of CRT applications, only a single study applied the traditional method of CRT assessment to more than 30 communities (Plested et al conducted interviews in 102 communities in 1999 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been argued that complex health interventions need to be context-dependent to be most effective [12, 23, 40]. Within the context of Indigenous communities in Canada where the barriers encountered to providing optimal chronic care are numerous, sometimes unique and typically more exacerbated compared to their non-Indigenous counterparts, and resources are scarce [23, 4042] the wisdom held by healthcare providers working in a community with regards to implementation of an intervention should not be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Given the barriers present in Indigenous communities such as availability and accessibility of primary healthcare services and professionals, appropriate and effective intervention strategies that take into account contextual factors in their planning and evaluation are needed to maximize improvements and increase the likelihood of success and sustainment [12, 13]. Readiness is a measure of the recognition, preparation, and/or action taken when facing an area that requires change or improvement [14] and has been identified as a critical contextual factor to incorporate into public health interventions in Indigenous communities [12, 15]. …”
Section: Introductionmentioning
confidence: 99%